Aldosterone-Induced Sarco/Endoplasmic Reticulum Ca2+ Pump Upregulation Counterbalances Cav1.2-Mediated Ca2+ Influx in Mesenteric Arteries - Salazar-Enciso, Rogelio; Guerrero-Hernández, Agustín; Gómez, Ana M.; Benitah, Jean-Pierre; Rueda, Angélica (Frontiers in Physiology, 2022)
In mesenteric arteries (MAs), aldosterone (ALDO) binds to the endogenous mineralocorticoid receptor (MR) and increases the expression of the voltage-gated L-type Cav1.2 channel, an essential ion channel for vascular contraction, sarcoplasmic reticulum (SR) Ca2+ store refilling, and Ca2+ spark generation. In mesenteric artery smooth muscle cells (MASMCs), Ca2+ influx through Cav1.2 is the indirect mechanism for triggering Ca2+ sparks. This process is facilitated by plasma membrane-sarcoplasmic reticulum (PM-SR) nanojunctions that drive Ca2+ from the extracellular space into the SR via Sarco/Endoplasmic Reticulum Ca2+ (SERCA) pump. Ca2+ sparks produced by clusters of Ryanodine receptors (RyRs) at PM-SR nanodomains, decrease contractility by activating large-conductance Ca2+-activated K+ channels (BKCa channels), which generate spontaneous transient outward currents (STOCs). Altogether, Cav1.2, SERCA pump, RyRs, and BKCa channels work as a functional unit at the PM-SR nanodomain, regulating intracellular Ca2+ and vascular function. However, the effect of the ALDO/MR signaling pathway on this functional unit has not been completely explored. Our results show that short-term exposure to ALDO (10 nM, 24 h) increased the expression of Cav1.2 in rat MAs. The depolarization-induced Ca2+ entry increased SR Ca2+ load, and the frequencies of both Ca2+ sparks and STOCs, while [Ca2+]cyt and vasoconstriction remained unaltered in Aldo-treated MAs. ALDO treatment significantly increased the mRNA and protein expression levels of the SERCA pump, which counterbalanced the augmented Cav1.2-mediated Ca2+ influx at the PM-SR nanodomain, increasing SR Ca2+ content, Ca2+ spark and STOC frequencies, and opposing to hyperpolarization-induced vasoconstriction while enhancing Acetylcholine-mediated vasorelaxation. This work provides novel evidence for short-term ALDO-induced upregulation of the functional unit comprising Cav1.2, SERCA2 pump, RyRs, and BKCa channels; in which the SERCA pump buffers ALDO-induced upregulation of Ca2+ entry at the superficial SR-PM nanodomain of MASMCs, preventing ALDO-triggered depolarization-induced vasoconstriction and enhancing vasodilation. Pathological conditions that lead to SERCA pump downregulation, for instance, chronic exposure to ALDO, might favor the development of ALDO/MR-mediated augmented vasoconstriction of mesenteric arteries.